2008
DOI: 10.2967/jnumed.108.052464
|View full text |Cite
|
Sign up to set email alerts
|

131I Effective Half-Life and Dosimetry in Thyroid Cancer Patients

Abstract: 131 I treatment in thyroid cancer patients may induce side effects, including extrathyroidal cancer and leukemia. There are still some uncertainties concerning parameters that may influence the effective half-life of 131 I and the absorbed doses by extrathyroidal organs. Methods: Whole-body retention of radioiodine was measured in 254 patients, and repeated quantitative whole-body scans and measurements of the urinary excretion of 131 I were performed on 30 of these patients. Results: The mean effective half-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
59
1
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(75 citation statements)
references
References 19 publications
4
59
1
11
Order By: Relevance
“…Remy et al [10] reported that the mean T eff was 10.5 h in rhTSH patients and was 15.7 h in thyroid-hormone-withdrawal patients. The T eff of our patients (thyroid-hormone-withdrawal patients) was 16.0 h, which was similar to that reported by Pacilio et al [11].…”
Section: Discussionmentioning
confidence: 99%
“…Remy et al [10] reported that the mean T eff was 10.5 h in rhTSH patients and was 15.7 h in thyroid-hormone-withdrawal patients. The T eff of our patients (thyroid-hormone-withdrawal patients) was 16.0 h, which was similar to that reported by Pacilio et al [11].…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, the efficacy of radioiodine treatment is related to the radiation dose delivered to remnant and neoplastic thyroid tissue [19]. However, the significant radiation doses delivered to extrathyroidal tissues may induce side effects such as nausea and vomiting, sialadenitis and xerostomia, loss of taste, and bone marrow insufficiency [19].…”
Section: Discussionmentioning
confidence: 99%
“…Some important differences exist in this regard between LT 4 withdrawal and rhTSH stimulation. The iodine clearance in euthyroid state is considerably higher than in hypothyroidism [8,[13][14][15][16] for example. Therefore the biological whole-body half-life of 131 I is shorter under rhTSH stimulation than it is under withdrawal.…”
mentioning
confidence: 99%
“…Therefore the biological whole-body half-life of 131 I is shorter under rhTSH stimulation than it is under withdrawal. In contrast it is also known that the intrathyroidal 131 I half-life is longer during rhTSH stimulation than during LT 4 withdrawal [8,16,17]. This can be explained by the relatively short duration of the rhTSH stimulus, which only results in a modest secretion of thyroid hormone-bound radioiodine.…”
mentioning
confidence: 99%
See 1 more Smart Citation